2018
DOI: 10.1007/jhep08(2018)043
|View full text |Cite
|
Sign up to set email alerts
|

On p-adic string amplitudes in the limit p approaches to one

Abstract: In this article we discuss the limit p approaches to one of tree-level p-adic open string amplitudes and its connections with the topological zeta functions. There is empirical evidence that p-adic strings are related to the ordinary strings in the p → 1 limit. Previously, we established that p-adic Koba-Nielsen string amplitudes are finite sums of multivariate Igusa's local zeta functions, consequently, they are convergent integrals that admit meromorphic continuations as rational functions. The meromorphic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Gerasimov and Shatashvili showed that in limit p → 1 the well-known non-local effective Lagrangian (reproducing the tree-level p-adic string amplitudes) gives rise to a simple Lagrangian with a logarithmic potential [21]. In [7], we show that the Feynman amplitudes of this last Lagrangian are precisely the Denef-Loser amplitudes.…”
Section: Introductionmentioning
confidence: 58%
“…Gerasimov and Shatashvili showed that in limit p → 1 the well-known non-local effective Lagrangian (reproducing the tree-level p-adic string amplitudes) gives rise to a simple Lagrangian with a logarithmic potential [21]. In [7], we show that the Feynman amplitudes of this last Lagrangian are precisely the Denef-Loser amplitudes.…”
Section: Introductionmentioning
confidence: 58%
“…With the pre-amplitude in hand, we are ready to carry out the two contour integrals in (4.46) to obtain the full Mellin amplitude. One way to do this is to close both contours to the right, and sum over the residues in the c A plane, which occur at 54) and then sum over the residues in the c B plane, occurring at…”
Section: Diagrams With Two Internal Linesmentioning
confidence: 99%
“…Actually, the previous equations just give account of the change of variables rule as x → x ′ , in the integral (9), that is…”
Section: P-adic Analytic Manifolds and Resolution Of Singularitiesmentioning
confidence: 99%
“…Then they used these functions to regularize the Koba-Nielsen amplitudes. In [9], the authors discussed the limit p approaches to one of tree-level p-adic open string amplitudes and its connections with the topological zeta functions. There is empirical evidence that p-adic strings are related to the ordinary strings in the limit p → 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation